Pemanfatan Arduino untuk Penentuan Kapasitansi Kapasitor pada Perbaikan Faktor Daya - Hermawan, Rheksi; , Dr. Ratnasari Nur Rohmah, S.T., M.T (2016)
The power factor is one of important value in the alternating electric calculation. This value will change according to the existing load on the electricity. This value also indicates how efficiently power is used. In ideal conditions, the best electric power factor is 1. However, in practice, this ideal can not be achieved because due to the equipment itself is not ideal. Achievement of the best that can be achieved is 0.99. One of the causes of poor power factor is inductive load. This load draw current more than a resistive load because there is manufacturing magnetic field process which effect to the work of this load does not correspond to the current consumed. This research will try to find a solution to the power factor resulting from the inductive load can be improved. Power factor improvement process is done by adding a capacitive load power. Capacitive power is obtained by installing capacitors at the load. This research will design a device which can determine the value of the capacitor in accordance with the load so that the power factor can be improved. This device is built from a voltage sensor, current sensor, phase difference sensor, and Arduino. Output data from all the sensors will be processed by the Arduino to calculate the corresponding value of the capacitor when the load is mounted. Based on the testing that was done, this research has succeeded to make a device works appropriately. Sensors that have been built have been compared to the measuring instrument HIOKI Power Meter 3286-20 and has a reading error by 3.13% for the voltage sensor, 4.85% for the current sensor, and 5.66% for the phase difference sensor. The capacitor value calculation results also have been tested at different loads. Results of testing the installation of capacitor has an error 0.875% against 0.99 power factor expectance. This indicates that the device is able to work properly.